2021
DOI: 10.1111/tbed.14433
|View full text |Cite
|
Sign up to set email alerts
|

Infectious bursal disease virus in free‐living wild birds: A systematic review and meta‐analysis of its sero‐viroprevalence on a global scale

Abstract: Infectious bursal disease virus (IBDV) is an economically important pathogen for poultry, whereas knowledge of its occurrence in non-poultry hosts is limited. The objective of this systematic review and meta-analysis is to summarize the up-to-date knowledge about the sero-viroprevalence of IBDV in wild birds on a global scale. A computerized literature research was performed on PubMed, Scopus, CAB Direct and Web of Science to find relevant publications, along with the screening of reference lists. Journal arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…In aquatic environments, intermediate avian hosts belonging to different feeding groups (herbivores, omnivores, carnivores, and insectivores) appear to be subjected to a similar infection probability [ 12 ]. In birds, several aquatic species are known hosts of relevant animal or zoonotic pathogens [ 13 , 14 , 15 , 16 , 17 ], including T. gondii [ 18 , 19 ]. Considering the ecology of waterfowl and the specialization as filter-feeders of some species, T. gondii infection in these animals suggests the presence of an oocysts-contaminated aquatic habitat.…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic environments, intermediate avian hosts belonging to different feeding groups (herbivores, omnivores, carnivores, and insectivores) appear to be subjected to a similar infection probability [ 12 ]. In birds, several aquatic species are known hosts of relevant animal or zoonotic pathogens [ 13 , 14 , 15 , 16 , 17 ], including T. gondii [ 18 , 19 ]. Considering the ecology of waterfowl and the specialization as filter-feeders of some species, T. gondii infection in these animals suggests the presence of an oocysts-contaminated aquatic habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were previously obtained by Fan et al [ 51 ], and Lian et al [ 52 ] using novel variant strains, Hb06v and SHG19, respectively. The entry of this nVarIBDV (genotype A2d) into Egypt is difficult to explain, but China has become the epicenter of nVarIBDV spreading to other parts of the world, with a strong correlation between virus transmission patterns and the flow of commercial trade in live poultry and products [ 53 ] or migratory birds that could be carriers or spreaders of IBDV [ 54 ]. Further studies should be undertaken to provide important insights into the origin, evolution and transmission of nVarIBDV in order to assist in the development of control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Infectious bronchitis virus (IBV) [ 3 , 4 , 5 ], Newcastle disease virus (NDV) [ 3 , 6 , 7 ], and avian influenza virus (AIV) [ 6 , 7 ] are common avian viruses circulating in migratory birds. In addition, a previous study showed moderate exposure of wild birds to infectious bursal disease virus (IBDV) [ 8 ]. The highly pathogenic avian influenza (HPAI) virus of the H5Nx subtype has been circulating in wild migrating birds over the last two decades and has become endemic in domestic poultry in several countries [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%